Adam Smith's answer to the Feldstein-Horioka paradox: The invisible hand revisited - Ayumu Yasutomi; Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2010)
In this paper, we show that Adam Smith pointed out the existence of the Feldstein-Horioka Paradox or Puzzle and even gave an explanation for it more than 200 years before the publication of Feldstein and Horioka (1980). Smith argues that it is the pursuit of their own security that leads owners of capital to invest their capital in their own country to as great an extent as possible and that it is the pursuit of security rather than the pursuit of profit that leads individuals to promote the good of society as a whole via the 'invisible hand.'
Keywords: B12; F21; F32; 330; Feldstein-Horioka paradox; Feldstein-Horioka puzzle; capital mobility; capital flows; saving; investment; Adam Smith; invisible hand; Feldstein-Horioka-Paradoxon; Kapitalmobilität; Sparen; Investition; Klassische Theorie; Dogmengeschichte